2016
DOI: 10.1007/s10661-016-5190-x
|View full text |Cite
|
Sign up to set email alerts
|

Massive land system changes impact water quality of the Jhelum River in Kashmir Himalaya

Abstract: The pristine aquatic ecosystems in the Himalayas are facing an ever increasing threat from various anthropogenic pressures which necessitate better understanding of the spatial and temporal variability of pollutants, their sources, and possible remedies. This study demonstrates the multi-disciplinary approach utilizing the multivariate statistical techniques, data from remote sensing, lab, and field-based observations for assessing the impact of massive land system changes on water quality of the river Jhelum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 83 publications
2
29
0
Order By: Relevance
“…A significant shift in the cultivation patterns from agricultural to horticultural land use has occurred in the basin mainly driven by economic considerations but partly attributed to the depleting water resources (Romshoo et al 2015;Showqi et al 2014). The area under the water intensive paddy cultivation has decreased significantly by about 700 km 2 during the last about 40 years only (Rather et al 2016) and the same has been either transformed into horticulture or built-up land. This has significantly reduced the demand for irrigation in the basin.…”
Section: Demography and Land System Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant shift in the cultivation patterns from agricultural to horticultural land use has occurred in the basin mainly driven by economic considerations but partly attributed to the depleting water resources (Romshoo et al 2015;Showqi et al 2014). The area under the water intensive paddy cultivation has decreased significantly by about 700 km 2 during the last about 40 years only (Rather et al 2016) and the same has been either transformed into horticulture or built-up land. This has significantly reduced the demand for irrigation in the basin.…”
Section: Demography and Land System Changesmentioning
confidence: 99%
“…Recently, the frequency of extreme rainfall events and floods has increased worldwide (Kundzewicz et al 2010;Lal et al 2001) including the NW Himalayas (Mishra and Srinivasan 2013;Valdiya 2011). The extreme rainfall event, as evident from the 7-day antecedent rainfall data observed in the Jhelum basin, turned into one of the worst disasters in the flood history of the Jhelum compounded by the existence of the injudicious socioeconomic structures (Hassan et al 2015) and massive land system changes (Rather et al 2016;Oza 2003) in the floodplains that interfered with the hydraulic and hydrological processes during the flooding (Negi 2001). The scenario was further worsened due to the dilapidated flood control structures and the institutional failure on managing the enormity of the extreme flooding.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis indicated that area under irrigation intensive rice paddies shows persistent signs of decline, whereas areas under orchards and built-up areas are increasing at unprecedented rates. The massive land system changes in the Kashmir region concerning agricultural lands, orchards, and built-up areas have been documented in many studies [39,40,87]. Although few studies suggest that the depleting streamflows are a significant factor driving the land system changes in Kashmir [88,89], the changes are also perhaps taking place due to economic considerations, especially given the fact that the production from apple orchards fetches more income compared to irrigation-intensive agriculture [46,[90][91][92][93].…”
Section: Discussionmentioning
confidence: 99%
“…Small decrease in AGB was observed in AS due to the presence of snow in satellite datasets of 1992, 2005 and 2013. AGB under OR is showing an increase especially in south and south-eastern part of Lidder valley, which could be attributed to the land system changes as the people have shifted from irrigation intensive paddy culture to cost-beneficial to profitable orchard cultivation Romshoo & Rashid 2014;Rather et al 2016). There is 2.7-fold increase in the land area under orchards from 1980-2013 in the study area.…”
Section: Phytosociology-based Agbmentioning
confidence: 99%
“…shows that 74.53 km 2 EF has degraded owing to varying pressures of forest degradation(Rather et al 2016). The other classes, which show changes from 1980-2013 are AG, BR, FL, AS, ML and WB.…”
mentioning
confidence: 99%